The craniotomy atlas - Raabe, Andreas; Meyer, Bernhard, 1962-; Schaller, Karl (Neurosurgeon); Vajkoczy, Peter; Winkler, Peter A. (Thieme, 2019)
"This atlas is a comprehensive compilation of common and frequently used craniotomies and includes all essential details for the training of neurosurgeons. Each craniotomy is described step-by-step in intraoperative color photographs and corresponding drawings, showing all details and landmarks mentioned in the text. The corresponding text gives technical instructions as well as detailed descriptions. The same structure will be used for the description of each craniotomy"--Provided by publisher